Preparation process and application of waste concrete recycled coarse aggregate water permeable brick
By loading the interface reinforcement on the surface of the regenerated concrete coarse aggregate and working with dihydrogen phosphate, the problem of low strength of concrete regenerated aggregates when preparing permeable bricks is solved, and the mechanical properties and freeze-thaw resistance of permeable bricks are improved.
Patent Information
- Application Number
- CN202510412290.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-03
- Publication Date
- 2025-05-02
- Estimated Expiration
- 2045-04-03
AI Technical Summary
The porosity of concrete recycled aggregates is high but the strength is low, which leads to problems such as deterioration of mechanical strength and reduced load-bearing capacity and durability when preparing permeable bricks.
By loading an interface reinforcement on the surface of the regenerated concrete coarse aggregate and working with dihydrogen phosphate, the bonding force between the regenerated aggregate and the permeable brick substrate is improved, and the mechanical properties of the permeable brick are improved.
It effectively improves the mechanical properties and freeze-thaw resistance of permeable bricks, enhances the binding force between regenerated coarse aggregates and gelling components, and solves the problem of insufficient mechanical strength and freeze-thaw resistance of traditional permeable bricks.
Smart Images

Figure CN119912223A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of cement-based permeable bricks, and in particular to a preparation process and application of waste concrete recycled coarse aggregate permeable bricks. Background Art
[0002] The information disclosed in this background technology section is only intended to enhance the understanding of the overall background of the invention, and should not necessarily be regarded as an admission or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art.
[0003] Urban Heat Island Effect refers to the phenomenon that the temperature in the city center is higher than that in the outer suburbs, thus forming a phenomenon similar to a high-temperature island. It is mainly caused by a large amount of artificial waste heat emission, a large amount of heat storage in buildings and roads in summer, and the reduction of green space, forests and water bodies. The sponge city concept has a good effect on alleviating the urban heat island effect. For example, permeable concrete or permeable bricks are used instead of traditional concrete materials as pavement materials, so that rainwater can penetrate into the stratum in time during rainfall to achieve storage and prevent waterlogging. When the temperature rises, the stored water is "released" into the atmosphere, which effectively promotes water circulation, reduces urban temperature, and alleviates the urban heat island effect.
[0004] As time goes by, a large number of buildings in cities need to be renovated, transformed, demolished and rebuilt, and this process will generate a large amount of waste concrete. The resulting environmental and waste disposal issues have become issues that must be addressed. Concrete recycled aggregate is made from the above-mentioned waste concrete, and is obtained through crushing, screening, cleaning, grading, etc. The resource utilization of recycled aggregate not only helps to dispose of a large amount of waste concrete in my country, but also reduces the impact on the environment. However, the porosity of concrete recycled aggregate is higher than that of natural aggregate, but the strength is lower, which leads to the deterioration of mechanical strength, decreased bearing capacity and durability when using this recycled aggregate to prepare concrete materials, limiting the application of concrete recycled coarse aggregate. Summary of the invention
[0005] In view of the above problems, the present invention provides a preparation process and application of waste concrete recycled coarse aggregate permeable bricks, which uses recycled coarse aggregate made from waste concrete as raw materials, not only making the permeable bricks have good permeability, but also improving the bonding force between the recycled aggregate and the permeable brick matrix, and improving the mechanical properties of the permeable bricks. Specifically, the technical solution of the present invention is as follows.
[0006] First, the present invention provides a preparation process of waste concrete recycled coarse aggregate permeable bricks, comprising the following steps: (1) Alkaline solution is added dropwise to a solution containing calcium ions and magnesium ions under stirring conditions. After precipitation is complete, nano-silicon dioxide is added, and then the obtained dispersion is subjected to a hydrothermal reaction. After completion, a solid product is separated, calcined, and then ground to obtain an interface strengthener.
[0007] (2) The interface strengthener is mixed with water to form a slurry, and the slurry is mixed with the recycled coarse aggregate for concrete, and then the recycled aggregate is dried to obtain the modified recycled coarse aggregate for concrete.
[0008] (3) Mixing silicate cement, silica fume, the modified concrete recycled coarse aggregate, rubber powder, dihydrogen phosphate, water reducer and mixing water to form a brick blank, and then curing to obtain a permeable brick.
[0009] Furthermore, in step (1), the molar ratio of calcium ions to magnesium ions is 1.5 to 1.8: 1. Optionally, the calcium ions are provided by at least one of calcium chloride, calcium nitrate, calcium acetate, etc. The magnesium ions are provided by at least one of magnesium chloride, magnesium sulfate, magnesium nitrate, etc.
[0010] Furthermore, in step (1), the alkali solution includes at least one of sodium hydroxide solution, potassium hydroxide solution, and ammonia water. The concentration of the alkali solution is not specifically limited in the present invention.
[0011] Furthermore, in step (1), the content of nano-silicon dioxide in the dispersion is 1.8-2.5 g / L.
[0012] Furthermore, in step (1), the temperature of the hydrothermal reaction is 160-220° C., and the time is 7-9 hours.
[0013] Furthermore, in step (1), the calcination temperature is 400-450° C. and the calcination time is 20-35 min. Optionally, the fineness of the interface strengthener is 350-500 mesh.
[0014] Furthermore, in step (2), the solid content of the slurry is 45-58 wt.%.
[0015] Furthermore, in step (2), the mass ratio of the recycled coarse aggregate to the slurry in the concrete is 10:1.3-2.
[0016] Furthermore, in step (2), the drying temperature is 70-100° C. and the drying time is 15-20 min.
[0017] Furthermore, in step (3), the proportions of the components are: 18-25 parts by weight of silicate cement, 1.2-1.7 parts by weight of silica fume, 72-105 parts by weight of modified concrete recycled coarse aggregate, 0.8-1.0 parts by weight of rubber powder, 0.55-0.7 parts by weight of dihydrogen phosphate, and 0.2-0.3 parts by weight of water reducer, and the mixing water is taken at a water-cement ratio of 0.28-0.35.
[0018] Furthermore, in step (3), the water reducer includes at least one of a polycarboxylic acid water reducer, a naphthalene-based water reducer, a lignin sulfonate water reducer, and the like.
[0019] Furthermore, in step (3), the dihydrogen phosphate includes at least one of ammonium dihydrogen phosphate, potassium dihydrogen phosphate, etc.
[0020] Furthermore, in step (3), the rubber powder has a fineness of 80-150 mesh. Preferably, the rubber powder is made of waste rubber.
[0021] Secondly, the present invention provides the use of waste concrete recycled coarse aggregate permeable bricks obtained by the preparation process in the fields of construction engineering, municipal engineering, road engineering, etc.
[0022] Compared with the prior art, the technical solution of the present invention has at least the following beneficial effects: (1) The permeable bricks of the present invention use recycled concrete particles as coarse aggregate, and use silicate cement and silica fume as cementing components to fill the gaps between the coarse aggregates, and then cement the coarse aggregates together to form permeable bricks. Compared with the traditional permeable bricks made of impermeable natural coarse aggregates and cement as raw materials, the permeable bricks of the present invention use the recycled coarse aggregates to provide permeable channels to achieve water permeability. The above-mentioned traditional permeable bricks use the gaps between natural coarse aggregates as permeable channels. Therefore, the present invention uses the structural characteristics of recycled coarse aggregates to convert them into permeable channels for permeable bricks, which not only achieves good permeability of the brick body, but also avoids the problem of low proportion of cementing components used to form permeable pores between natural coarse aggregates, which in turn causes insufficient mechanical strength and freeze-thaw resistance of the brick body. In addition, the rubber powder also helps to improve the freeze-thaw resistance of permeable bricks.
[0023] (2) The coarse aggregate in recycled concrete has a high water absorption rate, resulting in insufficient bonding strength between it and the permeable brick matrix, which in turn affects the mechanical strength of the permeable brick. This is because the coarse aggregate will gradually absorb the mixing water at the interface with the cementitious component during the hydration process. In addition, the hydration reaction of the silica fume requires the assistance of calcium hydroxide, a hydration product of the silicate cement, which causes the hydration reaction of the silica fume to start later. As a result, the hydration of the silica fume in the interface area cannot be fully carried out due to insufficient mixing water due to the late stage, and the content of the cementitious component formed is reduced, resulting in the formation of a weak interface area between the permeable brick matrix and the coarse aggregate. To this end, the present invention loads an interface strengthener on the surface of the recycled concrete coarse aggregate, which works together with the dihydrogen phosphate to effectively overcome the above-mentioned problems. This is because: first, the present invention prepares a liquid phase system containing a composite precipitate of calcium hydroxide and magnesium hydroxide, and then adds nano-silicon dioxide to carry out a hydrothermal reaction. The calcium hydroxide in the composite precipitate reacts with silicon dioxide to form hydrated calcium silicate. After further calcination, the magnesium hydroxide is converted into magnesium oxide, thereby forming an interface strengthener in which magnesium oxide and hydrated calcium silicate are mutually doped. When the recycled coarse aggregate with such an interface strengthener on the surface is used to prepare permeable bricks, during the curing process, on the one hand, the magnesium oxide and dihydrogen phosphate in the strengthener undergo a hydration reaction to form a hydration product with high strength and high bonding properties, which can effectively enhance the bonding force between the recycled coarse aggregate and the gelling component, and eliminate the weak interface area. At the same time, the strengthener also effectively avoids the problem that the fluidity of the slurry formed is reduced and it is not easy to cast and form due to the reaction of magnesium oxide and dihydrogen phosphate during the mixing and casting of the raw materials. On the other hand, the calcium silicate hydrate in the interface strengthener can act as a nucleation inducer to promote the hydration reaction of silica fume, so that the silica fume that starts the hydration reaction later can start the reaction at the early stage when the mixing water is relatively sufficient. This not only avoids the problem that the hydration reaction of silica fume cannot be fully carried out due to insufficient mixing water in the later stage, but also increases the content of the cementitious component at the interface, improves the bonding force between the recycled coarse aggregate and the cementitious component, and helps to further eliminate the weak area of the interface. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] The accompanying drawings constituting a part of the present invention are used to provide a further understanding of the present invention and do not constitute an improper limitation of the present invention. The embodiments of the present invention are described in detail below in conjunction with the accompanying drawings, wherein: Figure 1 This is a sample of the interfacial strengthener powder prepared in Example 1 below.
[0025] Figure 2 This is a picture of the permeable brick sample prepared in the following Example 1.
[0026] Figure 3 The following is a test diagram of the fluidity of the permeable brick slurry in Example 1.
[0027] Figure 4 This is a picture of the permeable brick sample prepared in the following Example 2.
[0028] Figure 5 This is a test diagram of the fluidity of the permeable brick slurry in the following Example 2.
[0029] Figure 6 This is a picture of the permeable brick sample prepared in the following Example 3.
[0030] Figure 7 This is a test diagram of the fluidity of the permeable brick slurry in the following Example 3.
[0031] Figure 8 This is a test diagram of the fluidity of the permeable brick slurry of the following Example 4. DETAILED DESCRIPTION
[0032] The present invention will be further described below in conjunction with specific examples. It should be understood that these examples are only used to illustrate the present invention and are not intended to limit the scope of the present invention. The experimental methods in the following examples without specifying specific conditions are usually carried out under conventional conditions or under conditions recommended by the manufacturer.
[0033] Unless otherwise defined, all professional and scientific terms used in the present invention have the same meaning as those familiar to those skilled in the art. The reagents or raw materials used in the present invention can be purchased through conventional channels. If not otherwise specified, the reagents or raw materials used in the present invention are used in a conventional manner in the art or in accordance with the product instructions. In addition, any method and material similar to or equivalent to the described content can be applied to the method of the present invention. Now, the technical solution of the present invention is further described in conjunction with specific embodiments.
[0034] Example 1 A preparation process of waste concrete recycled coarse aggregate permeable bricks, comprising the following steps: (1) Under continuous stirring conditions, an excess of sodium hydroxide solution is added dropwise to a solution containing calcium nitrate and magnesium nitrate (calcium to magnesium ion molar ratio = 1.6:1). After the precipitation is completely formed, nano-silicon dioxide is added to the system at a ratio of 1.8 g / L and ultrasonically dispersed for 5 minutes. The resulting dispersion is then added to a reactor and heated to 210°C for 7.5 hours for hydrothermal reaction. After completion, the solid product is filtered out and heated to 430°C for 30 minutes. After completion, it is ground and sieved to obtain an interface strengthener powder with a fineness of 500 mesh (such as Figure 1 as shown), for standby use.
[0035] (2) The interface strengthener and water are mixed and stirred to form a slurry with a solid content of 55 wt.%. Then, the recycled coarse aggregate of concrete with a particle size distribution between 5 and 8 mm is mixed with the slurry at a mass ratio of 10:1.5 and stirred to be uniform. Then, the obtained recycled aggregate is heated to 80°C and dried for 20 minutes to obtain the modified recycled coarse aggregate of concrete for later use.
[0036] (3) Take the following raw materials: 20 parts by weight of 42.5 ordinary Portland cement, 1.2 parts by weight of silica fume, 95 parts by weight of the modified concrete recycled coarse aggregate of this embodiment, 0.9 parts by weight of waste rubber powder with a fineness of 100 mesh, 0.6 parts by weight of potassium dihydrogen phosphate, and 0.22 parts by weight of polycarboxylic acid water reducer. After mixing the above raw materials evenly, add mixing water according to a water-cement ratio of 0.31 and stir evenly. Then pour the obtained slurry into the mold, demould it after hardening and forming, and place the obtained brick blank in a curing box for curing for 28 days. The curing temperature is set to 20°C. After completion, a permeable brick (such as Figure 2 as shown).
[0037] Performance test: 1. According to the "Concrete Physical and Mechanical Properties Test Method Standard" (GBT 50081-2019), the compressive strength and permeability coefficient of the permeable bricks were tested. 2. According to the "Permeable Pavement Bricks and Permeable Road Panels" (GB / T 25993-2010), the permeable bricks were subjected to 20 freeze-thaw cycles at -15°C, and then the compressive strength loss rate was calculated to measure the freeze-thaw resistance of the permeable bricks. 3. The fluidity of the slurry prepared in step (3) of this embodiment was tested (such as Figure 3 The results are shown in the following table: .
[0038] Example 2 A preparation process of waste concrete recycled coarse aggregate permeable bricks, comprising the following steps: (1) Under continuous stirring conditions, an excess of sodium hydroxide solution is added dropwise to a solution containing calcium nitrate and magnesium sulfate (calcium to magnesium ion molar ratio = 1.5:1). After the precipitation is completely formed, nano-silicon dioxide is added to the system at a ratio of 2.1 g / L and ultrasonically dispersed for 5 minutes. The resulting dispersion is then added to a reactor and heated to 160°C for 9 hours for hydrothermal reaction. After completion, the solid product is filtered out and heated to 400°C for 35 minutes. After completion, it is ground and sieved to obtain an interface strengthener powder with a fineness of 400 mesh, which is then set aside.
[0039] (2) The interface strengthener and water are mixed and stirred to form a slurry with a solid content of 45 wt.%. Then, the recycled coarse aggregate of concrete with a particle size distribution between 5 and 8 mm is mixed with the slurry at a mass ratio of 10:1.3 and stirred to be uniform. Then, the obtained recycled aggregate is heated to 70°C and dried for 20 minutes to obtain the modified recycled coarse aggregate of concrete for standby use.
[0040] (3) Take the following raw materials: 25 parts by weight of 42.5 ordinary Portland cement, 1.5 parts by weight of silica fume, 105 parts by weight of the modified concrete recycled coarse aggregate of this embodiment, 1.0 parts by weight of waste rubber powder with a fineness of 80 mesh, 0.7 parts by weight of potassium dihydrogen phosphate, and 0.3 parts by weight of sodium lignin sulfonate water reducer. After mixing the above raw materials evenly, add mixing water according to a water-cement ratio of 0.35 and stir evenly, then pour the obtained slurry into the mold, demould after hardening and forming, and place the obtained brick blank in a curing box for curing for 28 days. The curing temperature is set to 25°C. After completion, a permeable brick (such as Figure 4 as shown).
[0041] Performance test: The compressive strength, water permeability and freeze-thaw resistance of the permeable bricks prepared in this embodiment and the fluidity of the slurry prepared in step (3) of this embodiment (such as Figure 5 The results are shown in the following table: .
[0042] Example 3 A preparation process of waste concrete recycled coarse aggregate permeable bricks, comprising the following steps: (1) Under continuous stirring conditions, an excess amount of potassium hydroxide solution is added dropwise to a solution containing calcium chloride and magnesium chloride (calcium to magnesium ion molar ratio = 1.8:1). After the precipitation is completely formed, nano-silicon dioxide is added to the system at a ratio of 2.5 g / L and ultrasonically dispersed for 5 minutes. The resulting dispersion is then added to a reactor and heated to 220°C for 7 hours for hydrothermal reaction. After completion, the solid product is filtered out and heated to 450°C for 20 minutes. After completion, it is ground and sieved to obtain an interface strengthener powder with a fineness of 350 mesh, which is then used for later use.
[0043] (2) The interface strengthener and water are mixed and stirred to form a slurry with a solid content of 58 wt.%. Then, the recycled coarse aggregate of concrete with a particle size distribution between 5 and 8 mm is mixed with the slurry at a mass ratio of 10:2 and stirred to be uniform. Then, the obtained recycled aggregate is heated to 100° C. and dried for 15 minutes to obtain the modified recycled coarse aggregate of concrete, which is set aside.
[0044] (3) Take the following raw materials: 18 parts by weight of 42.5 ordinary Portland cement, 1.7 parts by weight of silica fume, 72 parts by weight of the modified concrete recycled coarse aggregate of this embodiment, 0.8 parts by weight of waste rubber powder with a fineness of 150 mesh, 0.55 parts by weight of ammonium dihydrogen phosphate, and 0.2 parts by weight of naphthalene-based water reducer. Mix the above raw materials evenly, add mixing water according to a water-cement ratio of 0.28, and stir evenly. Then pour the obtained slurry into a mold, demould it after hardening and forming, and place the obtained brick blank in a curing box for curing for 28 days. The curing temperature is set to 25°C. After completion, a permeable brick (such as Figure 6 as shown).
[0045] Performance test: The compressive strength, water permeability and freeze-thaw resistance of the permeable bricks prepared in this embodiment and the fluidity of the slurry prepared in step (3) of this embodiment (such as Figure 7 The results are shown in the following table: .
[0046] Example 4 A preparation process of waste concrete recycled coarse aggregate permeable bricks, comprising the following steps: (1) Mix 400-mesh magnesium oxide powder with water and stir evenly to form a slurry with a solid content of 45 wt.%. Then, concrete recycled coarse aggregate with a particle size distribution between 5 and 8 mm is mixed with the slurry at a mass ratio of 10:1.3 and stirred evenly. Then, the obtained recycled aggregate is heated to 70°C and dried for 20 minutes to obtain modified concrete recycled coarse aggregate.
[0047] (2) Take the following raw materials: 25 parts by weight of 42.5 ordinary Portland cement, 1.5 parts by weight of silica fume, 105 parts by weight of the modified concrete recycled coarse aggregate of this embodiment, 1.0 parts by weight of waste rubber powder with a fineness of 80 mesh, 0.7 parts by weight of potassium dihydrogen phosphate, and 0.3 parts by weight of sodium lignin sulfonate water reducer. Mix the above raw materials evenly, add mixing water at a water-cement ratio of 0.35, and stir evenly to obtain a slurry. Then, the fluidity of the slurry prepared in this embodiment is tested in the same manner as in the above embodiment 1 (such as Figure 8 The result is 151mm.
[0048] Example 5 A preparation process for waste concrete recycled coarse aggregate permeable bricks is the same as the above-mentioned embodiment 3, except that the present embodiment adopts the following method to prepare the interface strengthener: under continuous stirring conditions, an excess potassium hydroxide solution is added dropwise to a solution containing calcium chloride and magnesium chloride (calcium, magnesium ion molar ratio = 1.8:1), after the generated precipitation is complete, nano silicon dioxide is added to the system at a ratio of 2.5g / L and ultrasonically dispersed for 5min, and then the obtained dispersion is added to a reactor, heated to 220°C and kept warm for 7 hours for hydrothermal reaction, and after completion, the solid product is filtered out, dried to remove moisture, and then ground and sieved to obtain an interface strengthener powder with a fineness of 350 mesh.
[0049] Performance test: The compressive strength, water permeability coefficient and freeze-thaw resistance of the permeable bricks prepared in this embodiment and the fluidity of the slurry prepared in step (3) of this embodiment were tested using the same method as in the above embodiment 1. The results are shown in the following table: .
[0050] Example 6 A preparation process for waste concrete recycled coarse aggregate permeable bricks is the same as the above-mentioned embodiment 2, except that the present embodiment adopts the following method to prepare the interface strengthener: under continuous stirring conditions, an excess of sodium hydroxide solution is added dropwise to a solution containing calcium nitrate and magnesium sulfate (calcium, magnesium ion molar ratio = 1.5:1), and after the generated precipitation is complete, the obtained reaction system is added to a reactor and heated to 160°C and kept warm for 9 hours for hydrothermal reaction, after completion, the solid product is filtered out, and it is heated to 400°C and kept warm for 35 minutes, and after completion, it is ground and sieved to obtain an interface strengthener powder with a fineness of 400 mesh.
[0051] Performance test: The compressive strength, water permeability coefficient and freeze-thaw resistance of the permeable bricks prepared in this embodiment and the fluidity of the slurry prepared in step (3) of this embodiment were tested using the same method as in the above embodiment 1. The results are shown in the following table: .
[0052] Example 7 A preparation process of waste concrete recycled coarse aggregate permeable bricks, comprising the following steps: Take the following raw materials: 20 parts by weight of 42.5 ordinary Portland cement, 1.2 parts by weight of silica fume, 95 parts by weight of the modified concrete recycled coarse aggregate of Example 1, 0.6 parts by weight of potassium dihydrogen phosphate, and 0.22 parts by weight of polycarboxylic acid water reducer. After mixing the above raw materials evenly, add mixing water according to a water-cement ratio of 0.31 and stir evenly, then pour the obtained slurry into a mold, demould after hardening and forming, place the obtained brick blank in a curing box for curing for 28 days, and set the curing temperature to 20°C. After completion, a permeable brick is obtained.
[0053] Performance test: The compressive strength, water permeability coefficient and freeze-thaw resistance of the permeable bricks prepared in this embodiment and the fluidity of the slurry prepared in step (3) of this embodiment were tested using the same method as in the above embodiment 1. The results are shown in the following table: .
[0054] Example 8 A preparation process of waste concrete recycled coarse aggregate permeable bricks, comprising the following steps: Take the following raw materials: 20 parts by weight of 42.5 ordinary Portland cement, 1.2 parts by weight of silica fume, 95 parts by weight of recycled concrete coarse aggregate with a particle size distribution between 5 and 8 mm, 0.9 parts by weight of waste rubber powder with a fineness of 100 mesh, 0.6 parts by weight of potassium dihydrogen phosphate, and 0.22 parts by weight of polycarboxylic acid water reducer. After mixing the above raw materials evenly, add mixing water according to a water-cement ratio of 0.31 and stir evenly, then pour the obtained slurry into the mold, demould after hardening and forming, and place the obtained brick blank in a curing box for curing for 28 days, and the curing temperature is set to 20°C. After completion, a permeable brick is obtained.
[0055] Performance test: The compressive strength, water permeability coefficient and freeze-thaw resistance of the permeable bricks prepared in this embodiment and the fluidity of the slurry prepared in step (3) of this embodiment were tested using the same method as in the above embodiment 1. The results are shown in the following table: .
[0056] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention is described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A preparation process for waste concrete recycled coarse aggregate permeable bricks, characterized in that: The steps include: (1) adding alkali solution dropwise to a solution containing calcium ions and magnesium ions under stirring conditions, adding nano-silicon dioxide after precipitation is complete, and then subjecting the obtained dispersion to a hydrothermal reaction, separating a solid product after completion, calcining it, and then grinding it to obtain an interface strengthener; wherein: the molar ratio of the calcium ions to the magnesium ions is 1.5-1.8:1; the content of nano-silicon dioxide in the dispersion is 1.8-2.5 g / L; the calcination temperature is 400-450°C, and the time is 20-35 min; (2) mixing the interface strengthener with water to form a slurry, mixing the slurry with the recycled coarse aggregate for concrete, and then drying the recycled aggregate to obtain the modified recycled coarse aggregate for concrete; (3) Mixing silicate cement, silica fume, the modified concrete recycled coarse aggregate, rubber powder, dihydrogen phosphate, water reducer and mixing water to form a brick blank, and then curing to obtain a permeable brick.
2. The preparation process of waste concrete recycled coarse aggregate permeable brick according to claim 1, characterized in that: In step (1), the calcium ions are provided by at least one of calcium chloride, calcium nitrate and calcium acetate; Alternatively, in step (1), the magnesium ions are provided by at least one of magnesium chloride, magnesium sulfate, and magnesium nitrate.
3. The preparation process of waste concrete recycled coarse aggregate permeable brick according to claim 1, characterized in that: In step (1), the alkaline solution includes at least one of sodium hydroxide solution, potassium hydroxide solution and ammonia water.
4. The preparation process of waste concrete recycled coarse aggregate permeable brick according to claim 1, characterized in that: In step (1), the temperature of the hydrothermal reaction is 160-220° C. and the time is 7-9 hours; Alternatively, in step (1), the fineness of the interface strengthener is 350-500 mesh.
5. The process for preparing waste concrete recycled coarse aggregate permeable bricks according to claim 1, characterized in that: In step (2), the solid content of the slurry is 45-58 wt.%.
6. The process for preparing waste concrete recycled coarse aggregate permeable bricks according to claim 1, characterized in that: In step (2), the mass ratio of the recycled coarse aggregate to the slurry in the concrete is 10:1.3-2; Alternatively, in step (2), the drying temperature is 70-100° C. and the drying time is 15-20 min.
7. The process for preparing waste concrete recycled coarse aggregate permeable bricks according to claim 1, characterized in that: In step (3), the proportions of the components are: 18-25 parts by weight of silicate cement, 1.2-1.7 parts by weight of silica fume, 72-105 parts by weight of modified concrete recycled coarse aggregate, 0.8-1.0 parts by weight of rubber powder, 0.55-0.7 parts by weight of dihydrogen phosphate, and 0.2-0.3 parts by weight of water reducer, and the mixing water is taken at a water-cement ratio of 0.28-0.
35.
8. The process for preparing permeable bricks made of recycled coarse aggregate from waste concrete according to any one of claims 1 to 7, characterized in that: In step (3), the water reducer includes: at least one of a polycarboxylate water reducer, a naphthalene-based water reducer, and a lignin sulfonate water reducer; Alternatively, in step (3), the dihydrogen phosphate includes at least one of ammonium dihydrogen phosphate and potassium dihydrogen phosphate.
9. The process for preparing waste concrete recycled coarse aggregate permeable bricks according to any one of claims 1 to 7, characterized in that: In step (3), the fineness of the rubber powder is 80-150 mesh.
10. Use of waste concrete recycled coarse aggregate permeable bricks obtained by the preparation process according to any one of claims 1 to 9 in construction engineering, municipal engineering or road engineering.
Citation Information
Patent Citations
Magnesium phosphate cement recycled aggregate structure concrete and preparation method thereof
CN104072091A
Activity excitant for inorganic solid waste building materials and preparation method thereof
CN110467368A
Regenerated environment-friendly concrete and preparation process thereof
CN115477503A
Recycled concrete and preparation method thereof
CN119019141A